Bridge across the Bosporus The Foreign Policy of Turkey (Johns Hopkins University Press, 2019)
Originally published in 1971. With Atatürk's guiding reforms, Turkey underwent a sweeping modernization of the country's administration. More specifically, by adopting the Latin alphabet, secularizing the country's governance, and importing European laws and jurisprudence, Mustafa Kemal Atatürk effectively reformed the Republic of Turkey into a secular, modern nation-state. In doing so, he introduced a number of foreign policy commitments. Ferenc A. Váli examines the flexibility of Turkey's foreign commitments in light of the country's modernization; depending on the circumstance, Turkey's foreign policy has wavered between Western alliance and neutrality. Examining Turkey's foreign policy in the twentieth century, Váli provides historical background for Turkey's transition form an empire to a nation-state. Váli also assesses Turkey's relations with NATO, Western allies, Russia, the Baltic States, and the Middle East. For his research, Váli conducted interviews with officials of the Turkish Ministry for Foreign Affairs, political party leaders, academics, journalists, and members of diplomatic missions.